Correction of Background Effect in Photographic Photometry - K. Purbosiswojo (Journal of Mathematical and Fundamental Sciences, 1963)
Ichtisar. Suatu metoda untuk memperbaiki hasil2 fotometri jang diperoleh dengan mempergunakan photometer Eichner telah disadjikan dibawah ini. Penggunaan metoda tsb. telah ditjobakan pada gugus bintang NGC 6530 untuk fotometer di Observatorium Warner and Swasey. Metoda ini djuga dapat digunakan pada bagian2 dari katja potret jang kepekatan emulsi daripada latar belakangnja ber-beda2.Abstract. A method to correct photographic magnitudes of stars embedded in nebulosities measured by making use of Eichner-photometers is presented. An application of the method was carried out on the Galactic Cluster NGC 6530 for the photometer of Warner and Swasey Observatory. The method is also applicable on parts of photographic plates which background-emulsion densities differ from that of the region of the standard sequence